Study on Trend of Biodegradability of Phenolic Compounds During Photo-Fenton Advanced Oxidation Process (Iranian Journal of Chemical Engineering)
Phenolic acids constitute a major group of pollutants which are recalcitrant to common biological treatment. In this study synthetic wastewater containing a mixture of p-coumaric and p-hydroxybenzoic acids was evaluated for photo-Fenton pretreatment. The changes in biodegradability (ratio of biochemical oxygen demand to total organic carbon (TOC)) and mineralization (TOC removal) were monitored. While there was a significant biodegradability enhancement during the photo-Fenton process, there was little mineralization (less than 6%) taking place over the course of oxidation. Longer oxidation time did not further improve the pretreatment; rather it decreased the biodegradability of the solution through complete mineralization of the biodegradable intermediates. Resin fractionation of treated solutions indicated an increase in the hydrophilic fraction and a decrease in the hydrophobic fraction. Indeed, there was a clear and direct correlation between the hydrophilic nature of the organics and the biodegradability of the solution, indicating that hydrophilic compounds are more biodegradable. The formation of aldehydes further supported the links between biodegradable and hydrophilic compounds